Game changer - Greenwald, Tom, 1962- (Amulet Books, 2018)
While thirteen-year-old Teddy fights for his life after a football injury at training camp, his friends and family gather to support him and discuss events leading to his coma. Told through dialogue, text messages, newspaper articles, transcripts, an online forum, and Teddy's inner thoughts.